1998
DOI: 10.1002/(sici)1097-0274(199807)34:1<15::aid-ajim3>3.0.co;2-p
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of needle-stick injury by the scooping-resheathing method

Abstract: Background The objective of this study was to determine the effects of teaching the scooping resheathing method on the incidence of needle‐stick injuries in medical students. Methods Before starting their first clerkship, 81 medical students were given a 15‐min lecture on the high incidence and dangers of needle‐stick injuries and a demonstration of the scooping‐resheathing method. The number of needle‐stick injuries that occurred during the 3‐month clerkship was compared with the number reported by 86 medical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 28 publications
(42 reference statements)
0
3
0
Order By: Relevance
“…Thus avoiding recapping of used needles is essential for preventing needle stick injury. Froom et al have also shown in his study that teaching one handed, scooping-resheathing method can reduce the risk of needle stick injury [23,24].…”
Section: Discussionmentioning
confidence: 77%
“…Thus avoiding recapping of used needles is essential for preventing needle stick injury. Froom et al have also shown in his study that teaching one handed, scooping-resheathing method can reduce the risk of needle stick injury [23,24].…”
Section: Discussionmentioning
confidence: 77%
“…34,35 The one handed 'scoop' technique for recapping has been promoted widely and there is evidence that it is highly effective, even for non-experience users. 36,37 The risk factors involved in NSIs have been extensively studied. Aiken et al 29 suggested that many of the NSIs occur during needle recapping which is in agreement with the findings of the current study.…”
Section: Discussionmentioning
confidence: 87%
“…However, many approaches such as recommendations against recapping and increasing the accessibility of disposal containers have failed to reduce the incidence of needle-stick injuries [ 25 ]. Froom et al proposed that a lecture stressing the dangers of needle-sticks and recommending the use of the scooping method was effective in reducing the risk of needle-stick injuries in medical students [ 26 ]. In this hospital, we carried out several preventive countermeasures, such as equipping HCWs with the necessary personal protective equipment, wearing gloves before contact with a patient’s blood and body fluids, a ban on recapping needles after use, eliminating unnecessary injections, using automatically retracting safety syringes, and disposing of sharps into a sharps container immediately after use.…”
Section: Discussionmentioning
confidence: 99%